Talquetamab-related dysgeusia in multiple myeloma compared to BCMA-targeted bispecifics and high-dose melphalan - Fleischer, Anna; Roll, Magdalena; Frenking, Jan; Panther, Franziska; Gelbrich, Götz; Strunz, Patrick-Pascal; Riedhammer, Christine; Peter, Jessica; Mersi, Julia; Waldschmidt, Johannes; Kortüm, Martin; Einsele, Hermann; et al. (Cancer medicine, 2025)
Background Dysgeusia is a side effect of the anti-GPRC5DxCD3 bispecific antibody talquetamab (TAL), but other myeloma treatments, such as high-dose melphalan (MEL) with autologous stem cell transplantation (ASCT), are also known to alter taste perception in patients with multiple myeloma (MM). This study investigates the spectrum, prevalence and severity of dysgeusia in patients receiving TAL and MEL and compares the results with anti-BCMA bispecifics as a control for T-cell-engaging therapies. Methods Gustatory and olfactory performance was assessed in 87 MM patients divided into three treatment groups: TAL (n = 26), MEL/ASCT (n = 35), and BCMA bispecifics (n = 26). Evaluations included Taste Strips, Sniffin' Sticks Identification Test 16, and comprehensive questionnaires on taste perception, dietary issues, quality of life (QoL), mood, and treatment compliance. Results TAL-treated patients exhibited severe taste impairment, with 96.2% reporting marked declines. Taste alterations were also observed in patients receiving MEL/ASCT and BCMA bispecifics, though these were less pronounced, affecting 62.9% and 30.8% of cases, respectively. Xerostomia incidence was highest in the TAL group. Patients considering discontinuation of TAL (30%) cited taste alterations as the primary reason. MEL was associated with higher incidences of nausea, vomiting, and appetite loss. Conclusion TAL-associated taste disturbances have a major impact on patients and require further investigation and mitigation strategies. Enhanced patient support, proactive monitoring, and targeted interventions are critical to improving the well-being and adherence of MM patients.